Validating the Vegetable Variety Navigator Decision-support Tool Using Recent On-farm Variety Trial Data - Caleb D. Wehrbein; Sam E. Wortman (HortTechnology, 2024)
Local variety trial data are necessary for informing growers how a specific variety might perform on their farm but there is a growing deficiency in these data, particularly for specialty crops. To address this issue, an online decision-support tool named the Vegetable Variety Navigator (VVN) was developed in 2020 to compile, analyze, and visually communicate publicly available broccoli (Brassica oleracea var. italica), cucumber (Cucumis sativus), and sweet pepper (Capsicum annuum) variety trial data. To validate the accuracy and predictive potential of the VVN, we conducted 16 on-farm variety trials for broccoli, cucumber, and sweet pepper between 2020 and 2022. Yield of each variety in a trial was compared with the mean of all other varieties in the same trial to calculate a mean relative yield (MRY). The difference between observed relative yield in the field and predicted relative yield from the VVN (ΔMRY) was used to assess the accuracy of three different VVN prediction strategies. Strategies included using data from the following: 1) the single geographically nearest trial, 2) the mean of the three geographically nearest trials, or 3) the mean of all available trial data regardless of location. Compared with random predictions of MRY for each variety (from within a normal distribution of MRY values in the VVN database), the VVN predictions reduced ΔMRY and improved the accuracy of relative yield predictions across varieties by up to 21% in broccoli, 51% in cucumber (depending on strategy), and 51% in sweet pepper. Results confirm the value of the VVN as a decision-support tool for growers facing an ever-increasing number of crop variety options with less variety trial data. Future research and development are needed to improve the accuracy of the VVN by accounting for possible effects of crop types, management, and location on relative yield and quality.